Efektivitas Supply Chain Integration Terhadap Peningkatan Kinerja Perusahaan Industri Dalam Lingkup Global - Putri Aulia Rosmayani; Eva Nuragustin; Aghniya Choirunnisa; Rhaina Al Yasin; Anisya Febriyanti; Haikal Ghifary; Acim Heri Iswanto (Pusat Riset dan Inovasi Nasional, 2023)
Currently, many industrial companies are growing rapidly and significantly. One indicator of a company's success is the ability to sustain. This means that companies need to have added value that refers to strategic alignment, interconnection of companies and supply chain partners. An integrated supply chain will increase the overall value generated. This shows that companies must meet consumer demand by working together to produce cheap, timely, and high-quality products. The purpose of this study is to get an overview of how much influence the implementation of supply chain integration has on improving the performance of industrial companies. This research uses a literature study method with literature searches, namely Google Scholar and Pubmed, selected between 2019-2022. The results of this study were obtained from eight research articles that fit the keywords and inclusion criteria. This study shows that supply chain integration provides supply chain visibility and overall operating performance. This research can be concluded that supply chain integration has a direct effect on company performance. Thus, the higher the supply chain integration, it will provide better supply chain performance and certainly an increase in performance in industrial companies in producing a product.